Evolving Business Intelligence and Data Analytics in Higher Education. Issue 178 (23rd November 2018) - Drake, Brent M.; Walz, Aaron
Abstract: Over the past 20 years, many colleges and universities have made significant progress in building data warehouses and implementing business intelligence tools to provide better access to administrative data that were previously locked away in enterprise systems. However, the data architectures from the 1990s and 2000s are aging as new technologies offer expanded possibilities to collect, manage, and engage with data, including tapping into sources of data that were not available using previous approaches. This is coming at a time where there are increasing demands from stakeholders across higher education (internal and external) to "see the data" in response to constricting sources of funding, pressure to make higher education more affordable, changing student populations, and increased focus on student success and on‐time graduation. This chapter starts with a look at the historical approaches most schools have taken, then explores new analytic opportunities for IR offices and the impact these new technologies have on its operations while providing support for data‐driven decision‐making. The chapter concludes with a look at the future of business intelligence (BI) and data analytics and what it means for higher education.